Efect of synthetic detergent «Ariel» on morphological parameters of the fish Danio rerio in the acute experiment (Eurasian Journal of Ecology, 2016)
The effect of synthetic detergent «Ariel» on morphology of gills, intestine, liver, kidneys of Danio rerio at concentrations of 40, 50, 60, 80 mg / l. in experimental conditions were studied. At a concentration of detergent «Ariel» 40 mg /l. in gills foci of necrosis, hemorrhage, clumping lamellae were observed; in organs of the gastrointestinal tract – desquamation of mucosal epithelium; micronecrosis areas in liver were detected; in kidney stromal edema, congestion of blood vessels were observed. At a concentration of detergent «Ariel» 50 mg / l. in gills on lamellae hemorrhage and foci of necrosis of epithelium were revealed; in the organs of the gastrointestinal tract marked desquamation of mucosal epithelium was observed and in the liver there were detected moderate congestion of blood vessels, focal necrosis of hepatocytes, necrosis of the epithelium of the bile ducts; in kidney there was observed focal necrosis of the epithelium of the renal tubules. At concentrations of «Ariel» of 60 mg / l. and 80 mg / l. exposure results in mass mortality of experimental fish, in all organs marked extensive necrosis was examined.
Keywords: synthetic detergent; morphology; concentrations; necrosis; mass mortality